Large cell neuroendocrine carcinoma with a solitary brain metastasis and low Ki-67: a unique subtype. Issue 12 (December 2019) - Hermans, B C M; Derks, J L; Groen, H J M; Stigt, J A; van Suylen, R J; Hillen, L M; van den Broek, E C; Speel, E J M; Dingemans, A-M C
Abstract : Introduction: Stage IV large cell neuroendocrine carcinoma (LCNEC) of the lung generally presents as disseminated and aggressive disease with a Ki-67 proliferation index (PI) 40–80%. LCNEC can be subdivided in two main subtypes: the first harboring TP53 / RB1 mutations (small-cell lung carcinoma (SCLC)-like), the second with mutations in TP53 and STK11 / KEAP1 (non-small-cell lung carcinoma (NSCLC)-like). Here we evaluated 11 LCNEC patients with only a solitary brain metastasis and evaluate phenotype, genotype and follow-up. Methods: Eleven LCNEC patients with solitary brain metastases were analyzed. Clinical characteristics and survival data were retrieved from medical records. Pathological analysis included histomorphological analysis, immunohistochemistry (pRB and Ki-67 PI) and next-generation sequencing ( TP53, RB1, STK11, KEAP1 and MEN1 ). Results: All patients had N0 or N1 disease. Median overall survival (OS) was 12 months (95% confidence interval (CI) 5.5–18.5 months). Mean Ki-67 PI was 59% (range 15–100%). In 6/11 LCNEC Ki-67 PI was ≤40%. OS was longer for Ki-67 ≤40% compared to >40% (17 months (95% CI 11–23 months) vs 5 months (95% CI 0.7–9 months), P  = 0.007). Two patients were still alive at follow-up after 86 and 103 months, both had Ki-67 ≤40%. 8/11 patients could be subclassified, and both SCLC-like ( n  = 6) and NSCLC-like ( n  = 2) subtypes were present. No MEN1 mutation was found. Conclusion: Stage IV LCNEC with a solitary brain metastasis and N0/N1 disease show in the majority of cases Ki-67 PI ≤40% and prolonged survival, distinguishing them from general LCNEC. This unique subgroup can be both of the SCLC-like and NSCLC-like subtype.